Konstruksi Realitas Multiportal: Agenda Setting dan Framing Humas Pemerintah Dalam Distribusi Informasi di Era Media Digital - Sudiartawan, I Wayan; Arjana, Ida Bagus Made (IAHN Gde Pudja Mataram, 2025)
Digital transformation is forcing government public relations to evolve from one-way information dissemination to sophisticated multi-platform engagement. However, a critical gap exists between strategic potential and practical implementation, particularly in resource-constrained contexts. This research aims to deconstruct multi-platform framing strategies and identify drivers and barriers to their execution. A case study approach was employed, utilizing triangulation through semi-structured interviews with PR officers, non-participant observation of social media activity, and documentary analysis of content from official platforms. The findings reveal a critical paradox that demonstrates a sophisticated understanding of multi-platform framing, strategically tailoring government messaging to emphasize distinct attributes of multi-portal reality construction practices. However, these strategies are hampered by resource gaps, leading to agenda rationing and reliance on other departments for content. Furthermore, these strategies remain largely one-way broadcasts, resulting in a striking engagement paradox where high follower numbers do not translate into meaningful public interactions, as citizen data indicates a preference for more entertaining content. This research contributes a Multiportal Agenda-Setting Model that illustrates the dynamic, limited process of government communication within a fragmented media ecology.